Food System Governance in the Cambodian Mekong Delta: Food Production, Food Security, Migration, and Indebtedness - Sithirith, Mak; Sok, Sao; de Silva, Sanjiv; Kong, Heng (MDPI, 2024)
Despite the government’s active promotion of rice production, a significant portion of the population still faces food insecurity. While existing literature often highlights the success of achieving rice surplus, few studies delve into the connections between rice surplus and food security, and critically analyze why food security is persistent. In addressing this issue, the study investigates the underlying causes of food insecurity amidst the government’s efforts to increase rice production. The study entails a comprehensive review of existing literature and an examination of food security in three provinces in the Cambodian Mekong Delta. It concludes that while rice intensification has led to increased rice production available for consumption, challenges persist in terms of access to and utilization of rice for food consumption. These challenges are attributed to increased production costs with minimal profit margins, indebtedness, migration, land grabs, water conflicts, and lack of institutional integration in food systems, compounded by the effects of climate change and environmental degradation. As a result, a farming household with one hectare of farmland cannot produce enough rice for food consumption. Consequently, young people opt to sell off their land to settle debts and seek employment opportunities in urban and overseas areas.